The Influence of the Use of AI in Mathematics Learning at the High School Level: A Systematics Literature Review - Widya Rahmatika; M Mursalin; Eri Saputra; Mutia Fonna (Electronic Journal of Education, Social Economics and Technology, 2025)
The application of artificial intelligence (AI) in mathematics learning at the high school (SMA) level is now an important innovation in the world of education. AI brings a number of benefits such as the ability to personalize the learning process, increase efficiency, and provide broad and fast access to learning materials. However, its utilization is inseparable from various challenges. This study aims to identify and analyze the problems of the use of AI in high school mathematics learning systematically through the Systematic Literature Review (SLR) method with the PRISMA approach to 15 selected scientific articles. The results of the study show that the use of AI raises problems at various levels, especially in students who experience a decrease in critical thinking skills, creativity, and learning independence due to dependence on technology and an increasing tendency to plagiarism and procrastination. Meanwhile, from the side of teachers and educational institutions, obstacles were found in the form of low digital skills, limited training, lack of infrastructure, and the absence of a curriculum that accommodates the use of AI to the maximum. Although AI is well received by students, its use in schools is still very limited, reflecting a gap between potential and implementation. In addition, ethical aspects, data privacy, and changes in the role of teachers are important concerns. Therefore, collaboration across teachers, educational institutions, policy makers, and parents is needed to ensure the use of AI that is wise, ethical, and able to support the development of students' character and thinking abilities optimally.